Nanomaterials synthesis : design, fabrication and applications - Pottathara, Yasir Beeran (Elsevier, 2019)
Nanomaterials Synthesis: Design, Fabrication and Applications combines the present and emerging trends of synthesis routes of nanomaterials with the incorporation of various technologies. The book covers the new trends and challenges in the synthesis and surface engineering of a wide range of nanomaterials, including emerging technologies used for their synthesis. Significant properties, safety and sustainability and environmental impacts of the synthesis routes are explored. This book is an important information source that will help materials scientists and engineers who want to learn more about how different classes of nanomaterials are designed.